Decomposition based least squares iterative estimation algorithm for output error moving average systems. Issue 4 (27th May 2014) - Zhang, Wenge
Abstract : Purpose: – The purpose of this paper is to solve the heavy computational problem of parameter estimation algorithm. Design/methodology/approach: – Presents a decomposition least squares based iterative identification algorithm. Findings: – Can estimate the parameters for linear or pseudo-linear systems and have lower computational burden. Originality/value: – This paper adopts a decomposition technique to solve engineering computation problems and offers a potential and efficient algorithm.